Analysis Of Marketing Strategies In Increasing Product Sales (Study On Home Business Brown Sugar Tulus Bersih Desa Cahaya Negeri) - Cindy Silvia Putri Claudia; Kharul Bahrun (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
This study aims to determine the marketing strategy used by Brown Sugar (GM) home products "Tulus Bersih 100%" in Cahaya Negeri Village, Rejang Lebong Regency. In this study, the author uses a qualitative approach as a first step, namely a research approach by researching on certain subjects and surveys using questionnaires given directly to brown sugar industry owners. Data collection through observation, interviews and documentation using SWOT analysis and data analysis techniques through data reduction, data presentation and drawing conclusions. The conclusion of this study can be stated that the marketing strategy of the Brown Sugar (GM) home product "Tulus Bersih 100%" located in Desa Cahaya Negeri Rejang Lebong Regency is that the product marketed is brown sugar which already has a logo as an identification mark and a brand, namely "Tulus Bersih 100%". While the price marketed is adjusted to the size and quality of brown sugar. Promotions carried out by business actors still utilize traditional methods and production and marketing sites are not yet strategic, still utilizing houses in alleys